A tri-modal biosensor based on alkyne-functionalized gold nanoparticles and molecular beacon for detection of resistance-related point mutations in epidermal growth factor receptor-tyrosine kinase inhibitors - Ding Tan; Haixin Long; Ya Wang; Wenjing Lin; Yiling Huang; Haijun Chen; Yu Gao (Molecular Biology Reports, 2026)

Mapping Maximum Floodwater Footprints from Sustained Flood Traces - Yiling Lin; Xie Hu; Xiekang Wang; Yunxia Zhang (Water Research, 2026)

The impacts of multidimensional urban greenness on incident dyslipidaemia and blood lipid profiles among adults: A 10-year longitudinal cohort study in Hong Kong - Yufei Liu; Siyi Chen; Changqing Lin; Yiling Zheng; Yuanyuan Yi; Jun Yang; Shiu Lun Au Yeung; Jun Ma; Weifeng Li; Tuan Quang Phan; Lingxin Hao; Cui Guo (Environmental Research, 2026)

A novel method of estimating phytoplankton absorption coefficient for inland waters based on OLCI using Sun-induced chlorophyll-a fluorescence - Wenyu Liu; Yiling Zheng; Jie Lin; Yunmei Li; Honglei Guo; Huaiqing Liu; Yuxin Zhu; Fangfang Chen; Heng Lü; Song Miao (Journal of Oceanology and Limnology, 2026)

Disruption of sphingolipid metabolism triggers lung vascular inflammation and aging-like changes under hypoxia through VDAC1-mediated mitochondrial DNA release - Jin Xu; YiLing Ge; Bin Zhang; SiYuan He; QingLin Cao; PeiJie Li; YingRui Bu; YunGang Bai; Lin Zhang; GuoDong Tan; Jin Ma; ManJiang Xie (Apoptosis, 2026)

Mechanisms, treatment strategies and predictive biomarkers of drug resistance in acute myeloid leukemia - Jianjian Zhuang; Yue Li; Yingqiong Zhang; Yiling Huang; Yijia Han; Nengming Lin; Yangling Li (Mutation Research - Reviews in Mutation Research, 2026)

Hybrid calcium carbonate nanoparticles incorporated with capsaicin for tumor therapy via calcium overload mediated mitochondria damage and endoplasmic reticulum stress - Yiling Li; Yiyin Zhang; Guoqiao Chen; Xiaolong Liu; Qiming Xia; Yixuan Li; Jing Yang; Guoqiao Xu; Jiayi Chen; Jun Chen; Guping Tang; Xiaoxiao Fan; et al. (Chemical Engineering Journal, 2026)

General strategy for efficient persistent RTP polymer over 3 s: luminophore with a moderate θn-π angle - Danman Guo; Tong Zou; Yiling Miao; Jinzheng Chen; Zhu Chen; Xiangyu Ge; Faxu Lin; Yi Zhang; Zhenguo Chi; Zhiyong Yang; Huahua Huang (Chemical Engineering Journal, 2025)

The advantages in crop yields and carbon footprints of maize-soybean relay strip intercropping - Zhidan Fu; Ping Chen; Ping Lin; Yiling Li; Kai Luo; Chao Gao; Tian Pu; Yuze Li; Yushan Wu; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Journal of Environmental Management, 2025)

Investigating soil trophic links in a peatland, northeast China: Dual stable isotope analysis (δ13C and δ15N) of microarthropods and their food sources - Dandan Liu; Yiling Lin; Haitao Wu (European Journal of Soil Biology, 2025)

Advanced oxidation process with hydrogen peroxide and sulfite for superfast degradation of micro-contaminants in drinking water - Han Chen; Tao Lin; Yuchen Wang; Feiyu Lu; Yiling Shi; Junding Yin (Journal of Hazardous Materials, 2025)

Deep learning MRI-based radiomic models for predicting recurrence in locally advanced nasopharyngeal carcinoma after neoadjuvant chemoradiotherapy: a multi-center study - Chunmiao Hu; Congrui Xu; Jiaxin Chen; Yiling Huang; Qingcheng Meng; Zhian Lin; Xinming Huang; Li Chen (Clinical & Experimental Metastasis, 2025)

The Translation Initiation Factor eIF2Bα Regulates Development, Stress Response, Amylase Production, and Kojic Acid Synthesis in the Fungus Aspergillus oryzae - Yiling Liu; Zixin Chen; Chaofeng Chang; Yifen Lin; Guiyi Zheng; Feng Zhang (Current Microbiology, 2025)

DNAzyme assisted single amplification for FEN1 activity detection using a personal glucose meter - Mingxi Li; Weijie Zang; Shuiliang Wang; Zhannuo Lin; Shu Liu; Yiling Chen; Xiaohui Ruan; Yuanfang Luo; Chao Xing; Chunhua Lu (Analytica Chimica Acta, 2025)

Occurrence, removal, and fate of benzothiazoles (BTHs) and benzotriazoles (BTRs) in two wastewater treatment plants in New York State, USA - Jingchuan Xue; Yiling Lin; Daoming Zhao; Kurunthachalam Kannan (Science of The Total Environment, 2024)

A multifunctional hydrogel with mild photothermal antibacterial and antioxidant properties based on quercetin and dopamine-coated zinc oxide nanoparticles for healing bacteria-infected wound - Yan Liu; Qinbin Ma; Lei Tang; Yiling Shen; Huancai Zhao; Xiaoxu Liu; Danqi Lin; Guiyin Zhou (Chemical Engineering Journal, 2024)

Occurrence and bioaccumulation of parabens and their metabolites in the biota from a subtropical freshwater river ecosystem: Implications for human exposure - Yiling Lin; Yanan Zhao; Yuxian Liu; Yongyin Lan; Jiamin Zhu; Yanpeng Cai; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue (Environmental Research, 2024)

An operational approach for large-scale mapping of water clarity levels in inland lakes using landsat images based on optical classification - Shijiao Lu; Yingchun Bian; Fangfang Chen; Jie Lin; Heng Lyu; Yunmei Li; Huaiqing Liu; Yang Zhao; Yiling Zheng; Linze Lyu (Environmental Research, 2023)

Analysis of influencing factors and prediction of China’s Containerized Freight Index - Xiaoying Tu; Yiling Yang; Yu Lin; Shiqun Ma (Frontiers in Marine Science, 2023)
China, as a major maritime nation, the China Containerized Freight Index (CCFI) serves as an objective reflection of the Chinese shipping market and an important indicator for understanding China’s shipping industry globally. The shipping market is a complex ecosystem influenced by various factors, including vessel supply and demand, cargo supply and demand relationships and prices, fuel prices, and competition from substitute and complementary markets. To analyze and study the state of the Chinese shipping market, we selected the CCFI as an indicator and collected data on six factors that may affect the overall shipping market. These factors include “ the China Coastal Bulk Freight Index(CCBFI)”, “the Baltic Dry Index(BDI)”, “the Yangtze River Container Freight Index”, “Global: Aluminum (minimum purity of 99.5%, London Metal Exchange (LME) spot price): UK landed price”, “Major Ports: Container Throughput”, and “Coal Price: US Central Appalachia: Coal Spot Price Index”. Then, we constructed an analyticaland predictive framework using Deep Neural Network (DNN), CatBoost regression model, and robust regression model to study the CCFI. Based on the R 2 results of the three models, it is evident that DNN provides the best analytical and predictive performance for the CCFI, accurately forecasting its changes. Additionally, the robust regression model indicates that “Global: Aluminum (minimum purity of 99.5%, LME spot price): UK landed price” has the greatest impact on the CCFI. Finally, from a business perspective, we provide some suggestions for China’s container shipping industry.

A smartphone-assisted “all-in-one” paper chip for one-pot noninvasive detection of salivary glucose level - Qian Lin; Jiaqi Huang; Yiling Zhang; Miaomiao Chen; Yuzhi Xu; Xiaoyong Zou; Si-Yang Liu; Zong Dai (Chemical Engineering Journal, 2023)

The mechanism of different cyanobacterial responses to glyphosate - Wei Lin; Zhenyan Zhang; Yiling Chen; Qi Zhang; Mingjing Ke; Tao Lu; Haifeng Qian (Journal of Environmental Sciences, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Pollution mechanisms and photochemical effects of atmospheric HCHO in a coastal city of southeast China - Taotao Liu; Yiling Lin; Jinsheng Chen; Gaojie Chen; Chen Yang; Lingling Xu; Mengren Li; Xiaolong Fan; Fuwang Zhang; Youwei Hong (Science of The Total Environment, 2023)

Knockdown of SOX9 alleviates tracheal fibrosis through the Wnt/β-catenin signaling pathway - Lei Gu; Anmao Li; Jing Lin; Yiling Gan; Chunyan He; Rui Xiao; Jiaxin Liao; Yishi Li; Shuliang Guo (Journal of Molecular Medicine, 2022)

Spatial–temporal variations and pollution risks of mercury in water and sediments of urban lakes in Guangzhou City, South China - Xiaojun Wang; Wei Zhong; Bingxiang Wang; Mingying Quan; Tianhang Li; Durui Lin; Shengtan Shang; Chan Zhu; Churan Zhang; Yiling Liao (Environmental Science and Pollution Research, 2022)

Source variation and tempo-spatial characteristics of health risks of heavy metals in surface dust in Beijing, China - Leiping Cao; Ruimin Liu; Yiling Zhou; Cong Men; Lin Li (Stochastic Environmental Research and Risk Assessment, 2022)

DNA Methylation Changes Induced in Rice by Exposure to High Concentrations of the Nitric Oxide Modulator, Sodium Nitroprusside - Xiufang Ou; Tingting Zhuang; Wenchao Yin; Yiling Miao; Bo Wang; Yunhong Zhang; Xiuyun Lin; Chunming Xu; Diter von Wettstein; Sachin Rustgi; Bao Liu (Plant Molecular Biology Reporter, 2015)